Intracellular complexes of the early-onset torsion dystonia-associated AAA+ ATPase TorsinA - Li, Hui; Wu, Hui-Chuan; Liu, Zhonghua; Zacchi, Lucia F.; Brodsky, Jeffery L.; Zolkiewski, Michal (My University, 2014)
A single GAG codon deletion in the gene encoding torsinA is linked to most cases of early-onset torsion dystonia. TorsinA is an ER-localized membrane-associated ATPase from the AAA+ superfamily with an unknown biological function. We investigated the formation of oligomeric complexes of torsinA in cultured mammalian cells and found that wild type torsinA associates into a complex with a molecular weight consistent with that of a homohexamer. Interestingly, the dystonia-linked variant torsinAΔE displayed a reduced propensity to form the oligomers compared to the wild type protein. We also discovered that the deletion of the N-terminal membrane-associating region of torsinA abolished oligomer formation. Our results demonstrate that the dystonia-linked mutation in the torsinA gene produces a protein variant that is deficient in maintaining its oligomeric state and suggest that ER membrane association is required to stabilize the torsinA complex.
Citation: Li, H., Wu, H.-C., Liu, Z., Zacchi, L. F., Brodsky, J. L., & Zolkiewski, M. (2014). Intracellular complexes of the early-onset torsion dystonia-associated AAA+ ATPase TorsinA. SpringerPlus, 3(1), 743. https://doi.org/10.1186/2193-1801-3-743
Keywords: Early-onset dystonia; TorsinA; AAA+ ATPase; Protein association